Anaesthesia provider volume and perioperative outcomes in total joint arthroplasty surgery. (November 2019) - Memtsoudis, Stavros G.; Wilson, Lauren A.; Bekeris, Janis; Liu, Jiabin; Poultsides, Lazaros; Fiasconaro, Megan; Poeran, Jashvant
Abstract: Background: While increased surgical-provider volume has been associated with improved outcomes, research regarding volume–outcome relationships within high-volume institutions and the role of anaesthesiologists is limited. Further, the effect of anaesthesia-care-team composition remains understudied. This analysis aimed to identify the impact of anaesthesiologist and surgeon volume on adverse events after total joint arthroplasties. Methods: We retrospectively identified 40 437 patients who underwent total joint arthroplasties at a high-volume institution from 2005 to 2014. The main effects of interest were anaesthesiologist and surgeon volume and experience along with anaesthesia-care-team composition. Multivariable logistic regression models were used to evaluate three outcomes: any complication, cardiopulmonary complication, and length of stay (>5 days). Odds ratios (ORs) and 99.75% confidence intervals (CIs) were reported. Results: Across all three models, anaesthesiologist volume and experience, and anaesthesia-care-team composition were not significant predictors. Surgeon annual case volume >50 was associated with significantly reduced odds of any complication (annual case volume: 50–149; OR: 0.80; CI: 0.66–0.98) and prolonged length of stay (OR: 0.69; CI: 0.60–0.80). Surgeon experience >20 yr was associated with significantly reduced odds of prolonged length of stay (OR: 0.85; CI: 0.75–0.95). Conclusions: Anaesthesiologist volume and experience, and anaesthesia-care-team composition did not impact the odds of an adverse outcome, although a higher surgeon volume was associated with decreased odds of complications and prolonged length of stay. Further study is necessary to determine if these findings can be extrapolated to less specialised, lower volume surgical settings.